Implementasi Kahoot dan Teams Games Tournament dalam Meningkatkan Motivasi dan Hasil Belajar Siswa terhadap Matematika - Lilik Mustofiyah; Markhamah Markhamah; A. Fathoni; Sutama Sutama; Yulia Maftuhah Hidayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The purpose of this study was to determine the implementation of Kahoot and Teams Games Tournament in improving student motivation and learning outcomes in the field of mathematics. The research method applied is a mixed method with a concurrent model. The subjects of this study were 34 grade 6 students. The data collection methods employed encompassed observation, questionnaires, interviews, and testing. Learning motivation was measured by applying a questionnaire that had previously been tested for validity and reliability, with a Likert scale (score 1-5). The interview used 10 questions, while the test instrument included pretest and posttest. Sampling was conducted using the purposive-sampling method. The results showed that the use of Kahoot and TGT increased students' learning motivation by 86%. In addition, the integration of Kahoot with TGT cooperative learning model improved the mathematics learning outcomes of grade VI students at MI Muhammadiyah Madiun City. The pre-test results showed 65.15% completeness, while the post-test reached 81.62%. Interviews and questionnaires indicated 100% of students were interested, active, and had positive emotional responses and a desire to repeat learning with this method. The integration of Kahoot and TGT proved to be an effective and fun learning tool.